Influence of NiO reduction on microstructure and properties of porous Ni-ZrO2 substrates - Podhurska, V.; Vasyliv, B. (Видавництво Львівської політехніки, 2012)
The changes of microstructure, strength, electrical conductivity and fracture micromechanisms of porous YSZ–Ni substrate as anode-supported solid oxide fuel cell (SOFC) material after the treatment in high temperature (600°C) reducing and oxidizing environments have been studied.
Keywords: SOFC anode material; redox; microstructure; strength; electrical conductivity